The development and validation of the health belief model questionnaire for measuring factors affecting adherence in the elderly with hypertension - Rodhiyatul Fithri, - (Walter de Gruyter, 2021)
Objectives This study aimed to validate the questionnaire on the health belief model questionnaire to assess health beliefs that could influence adherence to hypertension in the elderly.